2019
DOI: 10.3390/biom9010034
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Mononucleotide: Exploration of Diverse Therapeutic Applications of a Potential Molecule

Abstract: Nicotinamide mononucleotide (NMN) is a nucleotide that is most recognized for its role as an intermediate of nicotinamide adenine dinucleotide (NAD+) biosynthesis. Although the biosynthetic pathway of NMN varies between eukaryote and prokaryote, two pathways are mainly followed in case of eukaryotic human—one is through the salvage pathway using nicotinamide while the other follows phosphorylation of nicotinamide riboside. Due to the unavailability of a suitable transporter, NMN enters inside the mammalian cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 79 publications
0
84
0
Order By: Relevance
“…More recently, NMN was tested in rodents 39,136 . Compared with NR, the metabolism of orally administered NMN is not fully understood.…”
Section: Nicotinamide and Its Related Compounds For Human Diabetesmentioning
confidence: 99%
“…More recently, NMN was tested in rodents 39,136 . Compared with NR, the metabolism of orally administered NMN is not fully understood.…”
Section: Nicotinamide and Its Related Compounds For Human Diabetesmentioning
confidence: 99%
“…Recently, human clinical trials have indicated that supplementation with the NAD + precursor nicotinamide riboside (NR) is well tolerated, elevates NAD + levels in healthy adults, and reduces the levels of circulating inflammatory cytokines in patients [ 131 , 132 ]. Another NAD + precursor, nicotinamide mononucleotide (NMN), also increases NAD + levels in mitochondria and protects mitochondria [ 133 ]. These findings suggest that NAD + precursors are potential clinical drugs for PD treatment.…”
Section: Lysine Acetylation Of Nonhistone Proteins In Pd Pathogenementioning
confidence: 99%
“…Nicotinamide mononucleotide (NMN) is one of the intermediates in NAD+ biosynthesis and is a bioactive nucleotide formed by the reaction between a phosphate group and a nucleoside containing ribose and nicotinamide (NAM) (Poddar et al, 2019). NAM is directly converted to NMN by nicotinamide phosphoribosyltransferase (NAMPT).…”
Section: Introductionmentioning
confidence: 99%
“…NAM is directly converted to NMN by nicotinamide phosphoribosyltransferase (NAMPT). The molecular weight of NMN is 334.221 g/mol (Poddar et al, 2019). There are two anomeric forms of NMN named alpha and beta, and the latter is the active form (Poddar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation